2005
DOI: 10.4321/s0210-48062005000100009
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la expresión de cerbB-2 en el adenocarcinoma de próstata

Abstract: 1) This study shows that 44% of all prostate cancer express the cerbB-2 oncoprotein with immunohistochemical technique. 2) These findings suggest that is necessary to standardize the immunohistochemical staining procedure with cerbB-2 in prostate adenocarcinoma. 3) The level of cerbB-2 expression was correlated with Gleason grade and clinical stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…(6) However, our results completely disagree with the results of 2 other studies that reported a 66% and 44% frequency of HER-2 overexpression in their patients. (4,5) Also, we found out that overexpression of this gene was not significantly related to the Gleason score. Fonseca and colleagues had the same result, but their sample size was small.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…(6) However, our results completely disagree with the results of 2 other studies that reported a 66% and 44% frequency of HER-2 overexpression in their patients. (4,5) Also, we found out that overexpression of this gene was not significantly related to the Gleason score. Fonseca and colleagues had the same result, but their sample size was small.…”
Section: Discussionmentioning
confidence: 75%
“…(6) In contrast to our findings, San Miguel Fraile reported a significant association between these 2 factor. (5) In a study on 216 patients, 97% of the HER-2-positive tumors had a Gleason score of 7 or higher. (7) The differences in the prevalence of HER-2 overexpression reported by the above studies might be due to the technical variations in the evaluation methods of the gene expression such as the antigen preservation, antigen retrieval techniques, antibody selection, and sampling for immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation